In Vitro Anthelmintic Activity of Crude Extracts of Aerial Parts of Cissus quadrangularis L. and Leaves of Schinus molle L. against Haemonchus contortus. (19th December 2017) - Zenebe, Selamawit; Feyera, Teka; Assefa, Solomon
Abstract : Background . Haemonchus contortus, the causative agent of Haemonchosis, is the most economically important parasite in small ruminant production. Control with chemotherapy has not been successful due to rapid emergence of drug-resistant strains. There is a continuous search for alternative leads particularly from plants. The study aimed to evaluate the anthelmintic activity of crude methanolic extracts of leaves of Schinus molle and aerial parts of Cissus quadrangularis against H. contortus. Methods . Adult motility test and egg hatching inhibition assay were employed to investigate the in vitro adulticidal and egg hatching inhibitory effects of the extracts. Results . Higher concentrations of the extracts (10 and 5 mg/ml) had a significantly superior adulticidal activity (p < 0.05 ) compared to the negative control and lower concentration levels, which was comparable to albendazole . Similarly, the relative egg hatch inhibition efficacy of S. molle and C. quadrangularis extracts indicated a maximum of 96% and 88% egg hatch inhibition, respectively, within the 48 hrs of exposure at 1 mg/ml. Conclusion . The current study evidenced that the crude methanolic extracts of the plants have promising adulticidal and egg hatching inhibitory effects against H. contortus .